TRAUMA AND RECOVERY IN SELECTED POEMS OF MILK AND HONEY BY RUPI KAUR - Bakri, Sri Maulidya; Bakri, Fitriyani (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to analyze how the experience of trauma and the process of trauma recovery are represented in selected poems from the book Milk and Honey by Rupi Kaur. The objectives of this study are to (1) identify the depiction of trauma through Lucien Goldmann's (1977) Genetic Structuralism approach, and (2) examine the process of recovery from trauma based on Judith Herman's (2001) Trauma and Recovery theory. The researcher used a descriptive qualitative method and selected poems from the hurting and the healing section of Milk and Honey as primary data. The findings on the poems from the hurting section depict deep psychological trauma through fragmented language and minimalist style. Using Goldmann's genetic structuralism, the researcher found that the trauma depicted in the poems reflects not only personal suffering, but also the collective consciousness of women silenced by patriarchal structures. In addition, other findings show that the poems reflect the three main stages of trauma recovery proposed by Judith Herman: establishing a sense of safety, remembering and mourning, and reconnecting. These stages are found especially in some of the healing chapter poems, where characters express self-empowerment, healing, and emotional recovery after experiencing abuse, violence, and loss